Reducing the spurious oscillations in the lumped parameters model using low-pass filter - Araujo, A. R. J. de [UNESP]; Silva, R. C. da [UNESP]; Kurokawa, S. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
Voltages and currents in the transmission line are described by differential equations that are difficult to solve due soil and skin effect that has to be considered for accurate results, but it increases their complexity. Therefore there are some models to study the voltages and currents along in transmission line. The distributed parameters model that transforms the equations in time domain to the frequency domain and once the solutions are obtained, they are converted to time domain using the Inverse Laplace Transform using numerical methods. Another model is named lumped parameters model and it considers the transmission line represented by a pi-circuit cascade and the currents and voltages are described by state equations. In the simulations using the lumped parameters model, it can be observed the presence of spurious oscillations that are independent of the quantity of pi-circuits used and do not represent the real value of the transient. In this work will be projected a passive low-pass filter directly inserted in the lumped parameters model to reduce the spurious oscillations in the simulations, making this model more accurate and reliable for studying the electromagnetic transients in power systems.
Keywords: Electromagnetic transients; Transmission lines; Distributed parameters; Lumped parameters; Low-pass filter